THE KNOWLEDGE OF BREASTFEEDING MOTHERS ABOUT THE USE OF CONTRACEPTION OF KB INJECTION AT TABARINGAN HEALTH CENTER MAKASSAR - irawati irawati (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
ABSTRACT Introduction: Injected contraception is a method used to avoid pregnancy through the hormonal injection. The hormonal contraception, type KB injection is more and more used in Indonesia because of its effective work, its use is practical, its price is relatively cheap, and safe. Method: The research type used is the Cross Sectional Study, and the aimis to find out the correlation between the independent variable and the dependent cariable. The research population includes all the mothers who come for examination of their pregnancy and have used injected KB at Tabaringan Health Center, Makassar, and from them, 59 are prepared to become respondents, and therefore chosen using the Accidental Sampling technique. Result: The research results indicated that 43 mothers have good knowledge, while 16 mothers have less knowledge. The research also reveals that 42 mothers have used injected KB while 17 mothers have not used injected KB, that there is a correlation between the mothers' knowledge and the contraception of injected KB at Tabaringan Health Center, Makassar with the value of p=0.009. Conclusion: Thus, it is expected that the nurses on duty at KB poly department should increase their performance and attention when giving extension especially about the injected contraception